Characterization of a Cyanobacterial Haloperoxidase and Evaluation of its Biocatalytic Halogenation Potential. (22nd September 2016) - Frank, Annika; Seel, Catharina Julia; Groll, Michael; Gulder, Tanja
Abstract: Vanadium‐dependent haloperoxidases (VHPOs) are a class of halogenating enzymes found in fungi, lichen, algae, and bacteria. We report the cloning, purification, and characterization of a functional VHPO from the cyanobacterium Acaryochloris marina ( Am VHPO), including its structure determination by X‐ray crystallography. Compared to other VHPOs, the Am VHPO features a unique set of disulfide bonds that stabilize the dodecameric assembly of the protein. Easy access by high‐yield recombinant expression, as well as resistance towards organic solvents and temperature, together with a distinct halogenation reactivity, make this enzyme a promising starting point for the development of biocatalytic transformations. Abstract : A handy haloperoxidase : The structural and functional characterization of a cyanobacterial vanadium‐dependent haloperoxidase is reported. Easy access by recombinant expression, robustness to organic reaction conditions, and a distinct bromination reactivity make this enzyme a promising tool for biocatalytic halogenations.